INTENSITAS KOMPETISI PASAR DAN BUDGET EMPHASIS PADA HUBUNGAN ANTARA PARTISIPASI DAN SENJANGAN ANGGARAN - Susanto, Yulius Kurnia (UI Scholars Hub, 2009)
The research examines the intensity o f market competition and budget emphasis on the relationship between budgetary participation and slack. Forty four managers from hotel industry in Jakarta had participated in the research. The collecting data employed used a questionnaire survey via electronic-mail. Data were analyzed using a two-way analysis o f variance. The results showed that the relationship between budgetary participation and slack were dependent on the intensity o f market competition and budget emphasis. Under low levels o f the intensity ofmarket competition, budgetary participation had a positive effect on budgetary slack, but under high levels it had a negative effect. The higher budget emphasis, the more positive was the relationship between budgetary participation and slack.